Analisis Evaluatif Kebijakan Lingkungan Hidup di Wilayah Sulawesi Barat 2016-2023 - Muhammad Rizky Prawira; Abdul Hafid; Sriwiyata Ismail Zainuddin; Andi Ismira; Muhammad Alif Mulky (Syntax Idea)
The implementation of environmental policies at the local or regional level can be reflected in the situation in West Sulawesi region. This research was conducted by highlighting various environmental policies that have been implemented by the West Sulawesi regional government in the last seven (7) years (2016-2023), then evaluating the effectiveness of these policies and the real impact they have produced in environmental preservation. The method used in this research is a combination of process tracing methods and semi-structured interviews. From the results of data collection and analysis, it was found that there had been some progress in terms of monitoring and law enforcement as well as increasing awareness of the young generation of West Sulawesi regarding environmental preservation. However, programs and policies on other issues such as reforestation of coastal lands, reforestation of forests, rehabilitation of critical lands, and waste management still need further improvement and refinement.